Volcanoes global perspectives - Lockwood, John P.; Cruz Reyna, Servando de la; Hazlett, Richard W. (Hoboken, NJ, USA Wiley-Blackwell, 2022)
"More than ten years have passed by since the First Edition of VOLCANOES was published in 2010. Our world of volcanology has changed in exciting ways over this decade, and we have much important new material to discuss in this Second Edition. Volcanoes have continued to erupt (some 61 eruptions with VEI magnitudes greater than 3 have taken place since 2010), and we are describing the largest of these and the ones that have had the most impact on society since the First Edition This new Edition contains more than 80 new photographs and figures to better illustrate volcanic features and processes, with an updated Bibliography that includes important papers describing recent eruptions and new findings. Professor Servando de la Cruz-Reyna of the National University of Mexico has joined us as a co-author, and this edition benefits greatly from his long experience in applying statistical tools to analyze volcanic hazards and risk, as well as his invaluable Latin American perspectives on volcanic activity. In the first introductory chapter, Servando, Rick and I describe our personal experiences with specific eruptions that we have learned from, eruptions that have taught particularly important lessons for volcanology. A visit to St. Pierre, Martinique in 2019 stimulated a renewed appreciation for the impact of the 1902 Mount Pelée eruption on the development of volcanology, and led to the realization that we had failed to pay enough attention to the Peléean class of volcanic eruptions in our First Edition - that failing is now addressed. Volcanologic research is improving the foundations of knowledge upon which all our science rests, and we briefly summarize the most important of these advances and new research tools developed over the past eleven years. The most productive of these new tools are remotely operated, constantly monitoring volcanoes and their impacts on the Earth's atmosphere from space and exploring new volcanic worlds beyond the bounds of Earth. Remotely Operated Vehicles (ROVs) are now widely available to understand better the most active volcanoes on Earth, those beneath the sea"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Volcanism -- Textbooks; Volcanology -- Textbooks; Volcanoes -- Textbooks